Ensuring Citizens’ Needs and Interests with Respect to General Education in Russia and Abroad: Management Approaches - Arinushkina, Anna; Neustroev, Sergey; Bakhtin, Maksim; Dovbysh, Svetlana (Journal of History Culture and Art Research, 2019)
The article deals with such aspects as “feedback” from direct consumers of educational services, which is the most adequate “cut” of the social and educational situation. The subject of the research is the socio-pedagogical situation and directions for improving the general education system in the Russian Federation at the federal and regional levels. Particular attention is paid to assessing the potential of diagnostic tools in the general education system, typing the demands of society and analyzing requests established through appeals of the citizens. The recommendations are given on the organization in the Russian Federation of a consulting service in the general education system at the federal, regional, and municipal levels as an element of the structure of executive bodies. The main conclusion of the study is the rationale for developing the consulting support for education management at all levels of the general education system.